2008
DOI: 10.1016/j.appet.2008.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The association between food cravings and consumption of specific foods in a laboratory taste test

Abstract: This pilot study tested the relation between food cravings and food intake in the laboratory. Participants (n = 91; mean BMI = 35.1 kg/m 2 ) completed the Food Craving Inventory to measure cravings for sweets, fats, carbohydrates, and fast food fats, and a taste test consisting of four foods (jelly beans, M&M's®, regular potato chips, and baked low-fat potato chips). Thereafter, participants could eat the items ad libitum. Specific food cravings were significantly correlated with consumption of corresponding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
56
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 8 publications
5
56
0
Order By: Relevance
“…Although not all food cravings are pathological, cravings are typically for foods that are high in fat, sugar, and carbohydrates such as chocolate, pizza, and fast foods (White et al, 2002). Researchers have also found that higher food cravings are associated with higher intake of respective food types craved and higher BMIs (Chao et al, 2014; Martin et al, 2008). Given the observed relationships among stress, food cravings, overeating, and BMI, it is possible that food cravings mediate the relationship between chronic stress and BMI.…”
Section: Food Cravings and Bmimentioning
confidence: 99%
“…Although not all food cravings are pathological, cravings are typically for foods that are high in fat, sugar, and carbohydrates such as chocolate, pizza, and fast foods (White et al, 2002). Researchers have also found that higher food cravings are associated with higher intake of respective food types craved and higher BMIs (Chao et al, 2014; Martin et al, 2008). Given the observed relationships among stress, food cravings, overeating, and BMI, it is possible that food cravings mediate the relationship between chronic stress and BMI.…”
Section: Food Cravings and Bmimentioning
confidence: 99%
“…However, it is uncertain if higher food cravings relate to higher overall, habitual consumption of the types of foods craved. In a laboratory-based study, Martin et al (2008) found that cravings for specific types of foods were significantly related to intake of similar food types among overweight and obese individuals (BMI > 29). They found that cravings for sweets correlated with intake of sweets (M & M’s® and jelly beans) but not with intake of fats (chips) and cravings for fats correlated only with intake of fats (regular potato chips).…”
Section: Introductionmentioning
confidence: 99%
“…Most clinical studies have failed to support the food restriction theory of food cravings and some studies have found that food cravings are actually decreased (rather than increased) during periods of caloric restriction(7). Furthermore, one study found that both a low-calorie food-based diet (LCD) and a restrictive very low calorie supplement-based diet (VLCD) led to significant decreases in food cravings with the reduction being greatest in the VLCD group(8).…”
Section: Introductionmentioning
confidence: 99%